2022
DOI: 10.3389/fnhum.2022.1044917
|View full text |Cite
|
Sign up to set email alerts
|

Association between electroconvulsive therapy and depressive disorder from 2012 to 2021: Bibliometric analysis and global trends

Abstract: BackgroundDepressive disorder is a chronic mental illness that is vulnerable to relapse, imposes a huge economic burden on society and patients, and is a major global public health problem. Depressive disorders are characterized by depressed mood, decreased energy and interest, and suicidal ideation and behavior in severe cases. They can be treated through pharmacotherapy and psychotherapy or physical treatments such as electroconvulsive therapy (ECT). In patients with suicidal ideation, behavior, or refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The University of Toronto, Duke University, and the University of California are the three institutions with the most publications in the field over the past ten years, each with 104. The current study' findings were similar to Cai et al [11] study according to most productive institutions, but the Mayo Clinic (the United States) (n=78), KU Leuven (Belgium) (n=66), Harvard University (the United States) (n=58) were the three institutions with the most publications in the field of ECT. This difference may be due to the fact that the study of Cai et al [11] was on ECT and depression.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The University of Toronto, Duke University, and the University of California are the three institutions with the most publications in the field over the past ten years, each with 104. The current study' findings were similar to Cai et al [11] study according to most productive institutions, but the Mayo Clinic (the United States) (n=78), KU Leuven (Belgium) (n=66), Harvard University (the United States) (n=58) were the three institutions with the most publications in the field of ECT. This difference may be due to the fact that the study of Cai et al [11] was on ECT and depression.…”
Section: Discussionsupporting
confidence: 89%
“…The degree of relatedness between unrelated authors is influenced by how often they cite a particular article; the more citations, the more related the authors are. [31] In a similar study, Cai et al [11] examined the relationship between ECT and depressive disorder from 2012 to 2021 with the bibliometric method. 2,184 publications were included in Cai et al [11] study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found rapid growth in publications after 2010; however, a lack of international scientific collaboration was also observed. Furthermore, a co-occurrence analysis was conducted by Cai et al (2022) regarding the connection between electroconvulsive therapy and depressive disorder research from 2012 to 2021. The study found that electroconvulsive therapy, treatment-resistant depression, bipolar disorder, hippocampus, efficacy and electrode location are key research hotspots.…”
Section: Literature Review and Identification Of Research Gapmentioning
confidence: 99%